2020
DOI: 10.1371/journal.pone.0230409
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease diagnosis from diffusion tensor images using convolutional neural networks

Abstract: Machine learning algorithms are currently being implemented in an escalating manner to classify and/or predict the onset of some neurodegenerative diseases; including Alzheimer's Disease (AD); this could be attributed to the fact of the abundance of data and powerful computers. The objective of this work was to deliver a robust classification system for AD and Mild Cognitive Impairment (MCI) against healthy controls (HC) in a low-cost network in terms of shallow architecture and processing. In this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…With respect to conventional ML methods, deep learning algorithms require little or no image pre-processing, and can automatically infer an optimal representation of the data from the raw images without requiring prior feature selection, thus resulting in a more objective and less biased process [67]. Few papers on the application of deep learning approaches, and in particular convolutional neural networks, in the classification or prediction of AD using DTI imaging data have been recently published achieving good results [68,69]. More comprehensive studies are needed to evaluate the advantages of these methods compared with more traditional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to conventional ML methods, deep learning algorithms require little or no image pre-processing, and can automatically infer an optimal representation of the data from the raw images without requiring prior feature selection, thus resulting in a more objective and less biased process [67]. Few papers on the application of deep learning approaches, and in particular convolutional neural networks, in the classification or prediction of AD using DTI imaging data have been recently published achieving good results [68,69]. More comprehensive studies are needed to evaluate the advantages of these methods compared with more traditional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that adopted a logistic regression model with neurite density index, orientation dispersion index, and CTh as features reported 0.72 AUC for CN and MCI and 0.91 AUC for CN and AD [ 35 ]. Other studies employing whole MD and gray matter map reported 79.6% accuracy with 0.84 AUC for CN and MCI and 93.5% with 0.94 AUC to CN and AD [ 36 ], 76% with 0.83 AUC for NC and AD [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, recent trends in AD diagnosis include the use of DL-based approaches. DL-based [7,11,12,[19][20][21] studies consider multimodal information for classifying AD and mAD from NC. The studies [7,22,23] use 3D patches from the whole brain to train and test a CNN model.…”
Section: Introductionmentioning
confidence: 99%